Self-care behaviors related to air pollution protection questionnaire: a psychometric analysis - Mehdi Mirzaei-Alavijeh; Farzad Jalilian; Elena-Niculina Dragoi; Razieh Pirouzeh; Laleh Solaimanizadeh; Shima Khashij (BMC, 2020)
Abstract Background Air pollution is an environmental health issue that has received much attention due to its harmful effects on public health. The aim of this study was to determine the psychometric properties of the self-care behaviors related to air pollution protection. To this mean, questionnaire responses provided by Iranian college students were analyzed and a Health Belief Model (HBM) determined. Methods The self-care behavior related to air pollution protection was determined from responses from 301 university students using test item characteristics, face validity, reliability (internal consistency) and construct validity. Moreover, we carried out an exploratory factor analysis (EFA) to determine the factorial structure and explained variance. Results Based on Eigenvalues of ≥1.00 and factor loadings of ≥0.40, seven factors were extracted. The calculated Kaiser-Meyer-Olkin value was 0.804. Overall, the seven factors explain 66.39% of the variance in the hypothesized model. Cronbach's alpha for the measured factors: the perceived susceptibility, severity, barriers, benefits, self-efficacy, cues to action and behavior were 0.85, 0.79, 0.86, 0.66, 0.74, 0.83, and 0.75, respectively. Conclusion The analysis of the questionnaire's reliability and validity properties resulted in good values. The questionnaire is a promising instrument to assess self-care behavior related to air pollution protection from the perspective of college students.